2016
DOI: 10.7547/14-095
|View full text |Cite
|
Sign up to set email alerts
|

Range of Motion and Plantar Pressure Evaluation for the Effects of Self-Care Foot Exercises on Diabetic Patients with and Without Neuropathy

Abstract: A home exercise program could be an effective preventive method for improving ROM for foot joints and plantar pressure distribution in diabetic patients independent of the presence of neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 18 publications
3
79
0
4
Order By: Relevance
“…Iunes et al found after the intervention a significant increase in static mean pressure in the left foot (from 29 to 31 kPa; P = .02), while no differences were seen for dynamic plantar pressure. Cerrahoglu et al observed reductions in one out of 12 measured areas for static barefoot peak pressure (right medial forefoot, 13% improvement) and four out of 12 measured areas for dynamic measures (medial forefoot, 12% improvement; lateral forefoot, 24% improvement; midfoot, 29% improvement, heel, 19% improvement) in a comparison of baseline vs 4 weeks after the intervention.…”
Section: Structured Education Aimed At Health Care Professionalsmentioning
confidence: 99%
“…Iunes et al found after the intervention a significant increase in static mean pressure in the left foot (from 29 to 31 kPa; P = .02), while no differences were seen for dynamic plantar pressure. Cerrahoglu et al observed reductions in one out of 12 measured areas for static barefoot peak pressure (right medial forefoot, 13% improvement) and four out of 12 measured areas for dynamic measures (medial forefoot, 12% improvement; lateral forefoot, 24% improvement; midfoot, 29% improvement, heel, 19% improvement) in a comparison of baseline vs 4 weeks after the intervention.…”
Section: Structured Education Aimed At Health Care Professionalsmentioning
confidence: 99%
“…There is no direct evidence to suggest that foot‐related exercises prevent DFU, as studies on this topic are non‐existent. Various forms of foot‐related exercises are possible when aiming to improve modifiable risk factors for foot ulceration such as plantar pressure distribution, neuropathy symptoms, deficits in foot sensation, foot‐ankle joint mobility, and strength . These exercises can include stretching and strengthening of the foot and ankle musculature and functional exercises such as balance and gait exercises and are provided or supervised by physical therapists or similarly trained professionals.…”
Section: Treating Risk Factors For Ulcerationmentioning
confidence: 99%
“…These exercises can include stretching and strengthening of the foot and ankle musculature and functional exercises such as balance and gait exercises and are provided or supervised by physical therapists or similarly trained professionals. Multiple RCTs and non‐controlled studies have shown some benefit of these exercises on a range of modifiable risk factors for foot ulceration, including plantar pressure, foot and ankle range of motion, and neuropathy symptoms …”
Section: Treating Risk Factors For Ulcerationmentioning
confidence: 99%
“…We therefore conclude that while foot‐ and mobility‐related exercises do not appear to help prevent foot ulcers, they can be considered safe to increase a patient's level of weight‐bearing activity without increasing the risk for ulceration. Other studies on this topic primarily aimed to reduce risk factors for ulceration, such as plantar pressure reduction or redistribution, but did not report ulcer outcomes . Considering the health advantages resulting from specific foot‐related exercises, or from general weight‐bearing activity, these interventions can be considered for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on this topic primarily aimed to reduce risk factors for ulceration, such as plantar pressure reduction or redistribution, but did not report ulcer outcomes . Considering the health advantages resulting from specific foot‐related exercises, or from general weight‐bearing activity, these interventions can be considered for this population. However, no definitive conclusions can yet be drawn because of the limited evidence available, and further research is strongly advised.…”
Section: Discussionmentioning
confidence: 99%